Algorithms And Methods Determination Of Acute Bioassay Lethal And Chronic Toxicity Water - Krainiukov, O.M. (Man and Environment. Issues of Neoecology)
Purpose. Determination of lethal levels of acute and chronic toxicity of water. Methods. Biotesting. Results. The paper presents the results of experimental studies within the implementation of which was developed algorithms and how to quantify the levels of lethal acute and chronic toxicity of water using bioassay techniques for tseriodafniyah. The classification scale based on a synthesis of a large array of many years of experimental data to determine the toxicity of more than 3600 samples of wastewater enterprises of various sectors of the economy and the quality of some 2,000 water samples in surface water basins Seversky Donets, Dnieper, Dniester, Danube, Southern Bug and Western Bug. Conclusions. For these bioassay methods, the following metrological characteristics: error bioassay results; reproducibility bioassay; standard operational control reproducibility bioassay results; range response test object